Computation of eigenfrequencies for equilibrium models including turbulent pressure - Sonoi, Takafumi; Ludwig, Hans-Günter; Caffau, Elisabetta (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics